Chilean 12th graders’ attitudes towards English as a foreign language - Gómez Burgos, Eric; Pérez Pérez, Sandra (Colombian Applied Linguistics Journal, 2015)
A favourable attitude towards a language is a crucial factor in the process of learning a foreign language (Shams, 2008). In light of this premise, this article reports on a case study conducted in two subsidised secondary schools that involved 154 students from Puerto Montt, Chile. A questionnaire of five dimensions was given to the participants in order to identify their attitude towards teachers’ methodology and language use in the English classroom, English as a subject at school, English as a global language, and learning EFL in Chile. Results indicated that the students’ attitudes towards English are favourable; however, the dimensions related to attitudes towards learning English and English as a subject at school obtained unfavourable responses. These findings reassert the notion that students appreciate English as a global language, but they are not committed to learning it at school.